Pengaruh Busi, Pilot Jet 35, dan Campuran Bahan Bakar dengan Kadar Alkohol terhadap Daya pada Mesin Motor 110 CC Menggunakan Karburator Aftermarket - Dzaky Darma Saputra; Bambang Irawan; Haris Puspito Buwono; Nike Nur Farida (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Dependence on fossil fuels, such as gasoline and diesel, has become a global issue that affects environmental sustainability and energy security. Increasing greenhouse gas emissions, decreasing natural resource reserves, and instability of global energy prices encourage the need for innovation in motor vehicle fuel systems. This study aims to assess fuel efficiency and engine performance on a 110 CC motorcycle with a standard compression of 10.7:1, by utilizing a mixture of RON 90 gasoline and alcohol. The main focus of the study is to compare the effect of varying alcohol content on engine power output, with mixtures of E12.5, E17.5, and E22.5. The method used is an experimental method with three variables, namely the independent variable (type and content of fuel mixture), the dependent variable (engine power), and the control variables (engine condition, temperature, and testing method). Testing was carried out using a combination of iridium spark plugs and standard spark plugs, as well as variations in Pilot Jet sizes 34 and 35 on aftermarket carburetors. Each combination was tested to determine its effect on the maximum engine power. The results showed that a blend of E12.5 fuel with Pilot Jet 35 and iridium spark plugs produced the highest power output compared to other tested combinations. This combination was proven to optimize combustion in the combustion chamber, thereby improving engine efficiency and performance. Conversely, increasing the alcohol content above E12.5 did not provide a significant increase and even tended to decrease power due to alcohol's lower calorific value than gasoline. The conclusion of this study is that the use of an aftermarket carburetor with Pilot Jet 35 and iridium spark plugs, combined with an E12.5 fuel blend, can be an effective alternative for improving the performance of a 110cc motorcycle. These findings are expected to serve as a reference for the development of more efficient and environmentally friendly blended fuel technology.